2021
DOI: 10.1038/s41467-021-24127-3
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular localisation of Mycobacterium tuberculosis affects efficacy of the antibiotic pyrazinamide

Abstract: To be effective, chemotherapy against tuberculosis (TB) must kill the intracellular population of the pathogen, Mycobacterium tuberculosis. However, how host cell microenvironments affect antibiotic accumulation and efficacy remains unclear. Here, we use correlative light, electron, and ion microscopy to investigate how various microenvironments within human macrophages affect the activity of pyrazinamide (PZA), a key antibiotic against TB. We show that PZA accumulates heterogeneously among individual bacteria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 58 publications
9
44
0
Order By: Relevance
“…Next, Mtb-associated LysoTracker intensity and Mtb intrabacterial pH were analysed by automated high-content microscopy ( Figure S1 ). A quantitative analysis in Mtb-infected MDM (median CTRL = 422.6; IQR CTRL = 334.9 and median ConA = 241.6; IQR ConA = 64.5, respectively) and Mtb-infected iPSDM (median CTRL = 1964.2, IQR CTRL = 1006.0 and median ConA = 929.3; IQR ConA = 1009.4, respectively) showed that the median Mtb-associated LysoTracker intensity was reduced by approximately 2-fold upon ConA treatment ( Figure 1A and Figure 1C ), confirming that endolysosomal acidification was impaired (Santucci et al, 2021). On the other hand, a quantitative analysis of Mtb intrabacterial pH in control or ConA-treated conditions were similar in both infected MDM ( Figure 1B ) and infected iPSDM ( Figure 1D ) with absolute median differences that were almost null (Δmedian pH-GFP = 0.035 and 0.016 respectively), suggesting that intracellular acidification does not impact Mtb intrabacterial pH in human macrophages.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…Next, Mtb-associated LysoTracker intensity and Mtb intrabacterial pH were analysed by automated high-content microscopy ( Figure S1 ). A quantitative analysis in Mtb-infected MDM (median CTRL = 422.6; IQR CTRL = 334.9 and median ConA = 241.6; IQR ConA = 64.5, respectively) and Mtb-infected iPSDM (median CTRL = 1964.2, IQR CTRL = 1006.0 and median ConA = 929.3; IQR ConA = 1009.4, respectively) showed that the median Mtb-associated LysoTracker intensity was reduced by approximately 2-fold upon ConA treatment ( Figure 1A and Figure 1C ), confirming that endolysosomal acidification was impaired (Santucci et al, 2021). On the other hand, a quantitative analysis of Mtb intrabacterial pH in control or ConA-treated conditions were similar in both infected MDM ( Figure 1B ) and infected iPSDM ( Figure 1D ) with absolute median differences that were almost null (Δmedian pH-GFP = 0.035 and 0.016 respectively), suggesting that intracellular acidification does not impact Mtb intrabacterial pH in human macrophages.…”
Section: Resultsmentioning
confidence: 64%
“…Strikingly, from the four different antibiotics tested, PZA was the only one able to induce changes in Mtb pH-GFP ratio, providing evidence that PZA displays intrabacterial pH-disruptive activity in Mtb-infected human macrophages (mean normalised pH-GFP ratio of 0.155; p -value ≤0.001) ( Figure 3C ). PZA/POA molecules require endolysosomal acidification to accumulate inside Mtb and display antimicrobial efficacy (Santucci et al, 2021). We hypothesized that this process is likely resulting from the conversion of POA (-) into its protonated form HPOA within acidic host-microenvironments ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can involve both the targets within the microbe and the host’s transporters when (as is common, e.g., [ 468 , 469 , 470 , 471 , 472 , 473 , 474 , 475 , 476 , 477 , 478 , 479 , 480 , 481 , 482 , 483 , 484 , 485 ]) the infective agents reside intracellularly. A particularly clear example is given by Mycobacterium tuberculosis , the causative agent of TB, where the very striking lack of correlation between in vivo and in vitro drug potencies is easily and necessarily explained via transporter activities [ 139 , 151 , 486 , 487 , 488 ]. Many orally prescribed antibiotics enter the host via SLC15 family members [ 489 , 490 ], while some of the relatively few known microbial uptake transporters for anti-infectives are listed in Table 1 .…”
Section: Introductionmentioning
confidence: 99%